2018
DOI: 10.17533/udea.rccp.v31n3a04
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Tropical Milking Criollo cattle of Mexico estimated from genealogy information

Abstract: Background: Genetic variability of populations is essential for their genetic conservation and improvement, and genealogy analysis is a useful tool to estimate it. Objective: To determine genetic variability and inbreeding levels in Tropical Milking Criollo (LT). Methods: This study analyzed the genealogy of LT using the ENDOG software. Registration certificates of 3,427 LT animals born between 1945 and 2013, and from 608 born between 1950 and 2013 were used. Two populations were defined: the first one with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
3
2
Order By: Relevance
“…However, compared to the present study, larger GI were reported in Kumamoto (9.4 yr) and Kouchi (10.4 yr) Japanese Brown cattle breeds (Honda et al, 2006). Differences of GI among breeds may be the result of variations in calving age, fluctuating environmental conditions throught the years in the tropic (Rosendo et al, 2018), number of years that sires and dams are used, and breeding objectives; for example, large GI are convenient in conservation breeding programs.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…However, compared to the present study, larger GI were reported in Kumamoto (9.4 yr) and Kouchi (10.4 yr) Japanese Brown cattle breeds (Honda et al, 2006). Differences of GI among breeds may be the result of variations in calving age, fluctuating environmental conditions throught the years in the tropic (Rosendo et al, 2018), number of years that sires and dams are used, and breeding objectives; for example, large GI are convenient in conservation breeding programs.…”
Section: Discussioncontrasting
confidence: 74%
“…However, sometimes this does not happen, since the depends not only on the F, but also on the number of equivalent generations (). Other authors have reported this situation; for example, Rosendo et al (2018) published N e of 68.1 for the total and 64.6 for the selection nucleus Tropical Milking Criollo cattle, but corresponding F were 1.07 and 2.14. Boichard et al (1997) indicated that F trend, although commolnly used to quantify the rate of genetic drift, has some limitations; particularly when the pedigree completeness is low.…”
Section: Discussionmentioning
confidence: 93%
“…The fa/fe ratio in this study was 0.46, which was notably lower compared to several other breeds, including Berrenda Colorada, Berrenda Negra, Morucha, Mertolenga, Lageana, and Tabapua, which exhibited ratios greater than 1 [27,46,[54][55][56][57]. Conversely, proportions in the Pinzgau cattle breed and the Marchigiana and Bosmara breeds in Brazil were similar, indicating a genetic bottleneck within the Negra Andaluza breed, affecting its genetic diversity, akin to observations in commercial dairy cattle breeds [58].…”
Section: Discussioncontrasting
confidence: 69%
“…The animal biodiversity includes the diversity of species that are living in a site, its genetic variability and the evolutionary ecological processes that occur at the level of ecosystems and landscapes of which these species interact ( Pariacote, 2000 ). The study of the biodiversity of the MG, its genetic structure and its relationship with other turkey populations is essential to understand its evolutionary potential, health, and sustainability ( Chassin-Noria et al, 2005 ; Rosendo Ponce et al, 2018 ). Presently, interest in the characterization of native turkey populations has begun, and some studies have been centered on external morphology ( Adeyemi and Oseni, 2018 ) by means of canonical discriminant analysis, but most of the interest has been dedicated to genetic characterization based on DNA markers, mainly microsatellites.…”
Section: Introductionmentioning
confidence: 99%